NILAI-NILAI PENDIDIKAN S?RAH AL-‘ALAQ - Madarik, Muhammad (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2018)
The discussion of the contents of the Qur'an surah Al-'Alaq verses 1 to 5 relating to Islamic education provides a clear picture of several things, among others: First, the core explanation in the surah Al-'Alaq provides information concerning the issue of divine knowledge, nature and humans. Second, in general, the content of educational values in the sura is a reflection of the understanding, goals, methods and basis of education. In this surah there is also a very basic relationship between aqidah (tauhid), and human (intellectual) skills which accumulate in the words iqra’ and ism rabbik. Implicitly, these two words reflect the existence of an important pillar in education which should be the foundation for every human being when seeking knowledge or even for the management of educational institutions. The word iqra’ is a symbol of activity processes that lead to ways to improve the mind intelligence of the mind and to develop the potential of human beings. Through the word iqra’ in this surah, Allah SWT is reminding everyone that the potential in the form of reason that has been given needs to be empowered. One of the most important educational values contained in these verses is a sign of the importance of reading, and information about the birth of new knowledge that has not been known before with such reading activities. While the word ism rabbik in this surah teaches the value of character education (khuluqiyah), so that the process of fostering, planting, and teaching that is done by humans is based on the belief in the manifestation of God Almighty. That way, all kinds of dynamics in the realm of education, including problems involving success or failure, are always repatriated to the will of Allah SWT and His power, so that the problems that arise do not cause anxiety, let alone despair.